Drug-Drug Interactions Between Lithium and Cardiovascular as Well as Anti-Inflammatory Drugs - Scherf-Clavel, Maike; Treiber, Susanne; Deckert, Jürgen; Unterecker, Stefan; Hommers, Leif (Pharmacopsychiatry, 2020)
Introduction Lithium is the gold standard in treating bipolar affective disorders. As patients become increasingly older, drug-drug interactions leading to decreased excretion of lithium represent a key issue in lithium safety. As no study considered the effect of comedications on lithium serum concentration in combination, we aimed to quantify the impact of drugs affecting renal blood flow and function and thus potentially interacting drugs (diuretics, ACE inhibitors, AT1 antagonists, and non-steroidal anti-inflammatory drugs) on lithium serum levels in addition to age, sex, and sodium and potassium serum levels as well as renal function.Methods Retrospective data of lithium serum levels were analyzed in 501 psychiatric inpatients (2008–2015) by means of linear regression modelling.Results The number of potentially interacting drugs was significantly associated with increasing serum levels of lithium in addition to the established factors of age, renal function, and sodium concentration. Additionally, absolute lithium levels were dependent on sex, with higher values in females. However, only NSAIDs were identified to increase lithium levels independently.Discussion Routine clinical practice needs to focus on drugs affecting renal blood flow and function, especially on NSAIDs as over-the-counter medication that may lead to an increase in lithium serum concentration. To prevent intoxications, clinicians should carefully monitor the comedications, and they should inform patients about possible intoxications due to NSAIDs.
Keywords: lithium; triple whammy; NSAIDs; pharmacokinetic Interaction